How doctoral students’ role perceptions influence advisor-advisee relationships and academic progress: a case study - Wu, Hechun; Kim, Jungyin (Frontiers in Psychology, 2025)
IntroductionThis qualitative research investigated how doctoral (Ph.D.) students’ role perceptions influenced their expectations and behaviors, thereby influenced advisor-advisee relationships and academic progress. Doctoral advising is essential for doctoral students’ academic progress. One of the factors to influence doctoral students’ academic progress is the advisor-advisee relationships. Under the guidance of Biddle’s Role Theory, the researchers aimed to find out how doctoral students’ perceptions of the advisors’ roles and their own roles influenced their advisor-advisee relationships. Doctoral advisor-advisee relationship can influence doctoral students’ academic progress.MethodsBy interviewing three Chinese Ph.D. students who studied in Korea, interview videos, emails, and messages between the participants and their advisors were collected as data. Data from the interviews were the main data resource. Other resources were used to support the data from interviews. These data were analyzed using qualitative methods, including transcription, coding, and member checking. The coding process was based on the transcription, and the member checking process ensured the validity the study.Results/findingsThe findings indicated that variations in participants’ role perceptions can significantly influence the advisor-advisee relationships, which in turn influenced academic progress.DiscussionThe patterns among the three participants showed that participants’ role perceptions influenced participants’ expectations and behaviors. Whether participants’ expectations were fulfilled, and whether participants’ behaviors were understood by the advisor influenced the advisor-advisee relationships. The advisor-advisee relationships influenced the participants’ learning experience and graduation, and further influenced the academic progress. Suggestions for advising Ph.D. students and limitations of this study were provided at the end of this study.